2007
DOI: 10.1016/s1808-8694(15)31125-3
|View full text |Cite
|
Sign up to set email alerts
|

Middle Latency Response Study of Auditory Evoked Potentials' Amplitudes and Lantencies Audiologically Normal Individuals

Abstract: We established average and standard deviation values for latency and amplitude parameters for components Na, Pa, Nb and Na-Pa and Pa-Nb, under conditions C3A1, C4A1, C3A2, C4A2, providing a parameter for the analysis and interpretation of this potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
(13 reference statements)
1
9
1
Order By: Relevance
“…Althen et al (2011) posited that the Na represented an early automatic deviant detection process, similar to the conclusion reached by Sonnadara et al (2006) -Cz reference. The Na in this study showed an anterior focus and a latency of 29 ms, longer than usually found (Neves et al, 2007), but this…”
Section: Accepted Manuscriptcontrasting
confidence: 73%
“…Althen et al (2011) posited that the Na represented an early automatic deviant detection process, similar to the conclusion reached by Sonnadara et al (2006) -Cz reference. The Na in this study showed an anterior focus and a latency of 29 ms, longer than usually found (Neves et al, 2007), but this…”
Section: Accepted Manuscriptcontrasting
confidence: 73%
“…These results are in agreement with previous studies of Purdy et al and Neves et al, in which latency values in our study for Na and Pa were more similar to those found by them [7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Discussionsupporting
confidence: 94%
“…According to Hall III [10] and Neves et al [7], the NaPa component would be the most robust and more visible. In the current study, we use both latency and amplitude measurement to compare the results between the SLI and control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The AMLR occurs after the auditory brainstem response (ABR) and consists of three main peaks: Na, Pa, and Nb (Goldstein and Rodman, 1967). The latency of the early phase enhancement matches that of the Na (~20 – 24 ms), Pa (~31 – 35 ms) and Nb (~42 – 50 ms) (Goldstein and Rodman, 1967; Neves et al, 2007). Since the P1 peaked at about 60 ms in this study, the later portions of this enhanced synchrony could partially reflect the P1 as well.…”
Section: Discussionmentioning
confidence: 54%